2016
DOI: 10.1002/bem.22014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cold atmospheric plasma treatment of cancer cells by static magnetic field

Abstract: It has been reported since late 1970 that magnetic field interacts strongly with biological systems. Cold atmospheric plasma (CAP) has also been widely studied over the past few decades in physics, biology, and medicine. In this study, we propose a novel idea to combine static magnetic field (SMF) with CAP as a tool for cancer therapy. Breast cancer cells and wild type fibroblasts were cultured in 96-well plates and treated by CAP with or without SMF. Breast cancer cells MDA-MB-231 showed a significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…22,[38][39][40][41][42] The synergistic use of CAP with other methods such as nanotechnologies, extra static magnetic field, as well as a pulsed electric field will enhance the efficacy of CAP treatment. [43][44][45][46][47][48][49][50] The anti-cancer mechanism in vitro is also complicated. Based on over 400 references, some general conclusions have been made so far.…”
Section: Introductionmentioning
confidence: 99%
“…22,[38][39][40][41][42] The synergistic use of CAP with other methods such as nanotechnologies, extra static magnetic field, as well as a pulsed electric field will enhance the efficacy of CAP treatment. [43][44][45][46][47][48][49][50] The anti-cancer mechanism in vitro is also complicated. Based on over 400 references, some general conclusions have been made so far.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of CAP‐based cancer therapy literature (condensed version; Table S1) revealed that very different experimental conditions have been used between different laboratories, and even between different experiments in the same laboratory . While some studies solely examined the effect of CAP on one cell line, others investigated CAP selectivity between normal and disease cells .…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of CAP‐based cancer therapy literature (condensed version; Table S1) revealed that very different experimental conditions have been used between different laboratories, and even between different experiments in the same laboratory . While some studies solely examined the effect of CAP on one cell line, others investigated CAP selectivity between normal and disease cells . Many studies that utilized more than one cell line for CAP‐based experiments used the same fluid for both cell lines (Table S1), while others used different media across different cell lines (Table S1) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations